STRENGTHENING ISLAMIC FAMILY LAW LITERACY AND STUDENT LEADERSHIP IN PESANTREN - Ahmad Musaddad (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This community service activity aims to enhance Islamic family law literacy and student leadership skills at Pondok Pesantren Al Falah, Situbondo, through a Participatory Action Research approach. The program includes learning that connects classical fiqh with Indonesian positive law, as well as training in deliberation simulations, public speaking, and conflict management. Among 30 participants, evaluation results indicate significant improvement: the average knowledge score increased from 58.2 to 78.5, the integration of fiqh-positive law rose from 52.0 to 74.3, and the average attitude score improved from 3.6 to 4.2 (on a 1-5 scale). Participation was recorded as high, with 93% attendance, 80% of participants actively engaged in each session, and an observational involvement score of 4.1/5. Findings demonstrate that the participatory approach effectively broadens students’ legal perspectives, strengthens leadership skills, and fosters the internalization of moderate attitudes and legal awareness. It is recommended to strengthen comparative fiqh–positive law materials in future activities, provide facilitator training, and conduct longitudinal evaluations to measure long-term impact.